The Development of Teaching Materials Based on Mobile Learning in English Learning for Elementary Schools - Agus Rofi'i; Sigit Vebrianto Susilo (STAI Hubbulwathan Duri, 2023)
This research is motivated by the low learning outcomes of elementary school students in learning English. This research aims to develop Android-based mobile learning teaching materials to support English language learning in elementary schools and improve student learning outcomes. This study uses Research and Development (RD) research using the Borg and Gall model, with the research sample being 5th-grade students of public elementary schools in West Java Province. Product validation tests were obtained from material, language, practitioners, and design experts and practitioners. Furthermore, the practicality test was obtained from the teacher and student response questionnaires throughout the learning process. Meanwhile, the effectiveness test was obtained through a limited trial using an experimental pretest-posttest control group design. The output of this research is to produce an application program for Android-based mobile learning teaching materials. Based on the study results, it can be concluded that Android-based mobile learning teaching materials are valid, practical, and effective for learning in elementary schools.